2011
DOI: 10.2217/fmb.11.131
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response in Candida Glabrata : Pieces of a Fragmented Picture

Abstract: Candida glabrata is closely related to yeast but obviously adapted to human commensalism. Communication with the environment is important to adjust allocation of resources between protection and proliferation in order to adapt to different situations in and outside of the host. Gene transcription regulated by environmental conditions is a major response strategy of simple fungal organisms. Differences to yeast include an extended repertoire of adhesive genes, and high drug, starvation and stress resistance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…Several lines of evidence suggest that these cells are of outstanding importance in the response against invasive Candida infections. PMN govern the transcriptional response of C. albicans to incubation in human blood (Fradin et al ., ) and induce various stress responses (Rubin‐Bejerano et al ., ; Enjalbert et al ., ; Jandric and Schuller, ; Fukuda et al ., ). Primary PMN confrontation assays have shown that PMN can differentiate between yeast and filamentous forms of C. albicans and PMN are the only host cell type known so far that can effectively inhibit filamentation of C. albicans after phagocytosis (Wozniok et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that these cells are of outstanding importance in the response against invasive Candida infections. PMN govern the transcriptional response of C. albicans to incubation in human blood (Fradin et al ., ) and induce various stress responses (Rubin‐Bejerano et al ., ; Enjalbert et al ., ; Jandric and Schuller, ; Fukuda et al ., ). Primary PMN confrontation assays have shown that PMN can differentiate between yeast and filamentous forms of C. albicans and PMN are the only host cell type known so far that can effectively inhibit filamentation of C. albicans after phagocytosis (Wozniok et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Its genome (ATCC 2001) covers 67 genes encoding putative adhesin-like GPI-modified cell wall proteins, including the Epa family with 17 members [59], and their expression is regulated. Moreover, C. glabrata cells carrying mutations in some loci show a rise in adherence to epithelial cells and are able to colonize organs more efficiently [60][61][62]. In fact, there are several factors tangled in the development of C. glabrata infection.…”
Section: Candida Glabrata-host Interactionsmentioning
confidence: 99%
“…Notably, both loci encode identical histone H3 and H4 proteins [20], and one H3-H4 gene locus is required for cell viability [21]. Owing to the phylogenetic relatedness between C. glabrata and S. cerevisiae, chromatin organization, DNA damage repair and stress response mechanisms are presumed to be similar between these two yeasts [22][23][24].…”
Section: Introductionmentioning
confidence: 99%